Ijtihad Tahqiq Al-Manat Implementation in The Fatwa of The Indonesian Ulama Assembly (MUI) in Southeast Sulawesi - Ahmad Ahmad; Andi Andhys Chaniago (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
The aims of the study are to examined the ijtihad method in the fatwa carried out by the Southeast Sulawesi MUI and to describe the Southeast Sulawesi MUI fatwa that uses the ijtihad tahqiq al-manat method. This qualitative investigation examines the text of the Southeast Sulawesi MUI fatwa. Various approaches are employed, including sociological, textual, and contextual approaches. The method of data collection employs a citation technique. This study's findings suggest that the Southeast Sulawesi MUI continues to implement a fatwa that will be strengthened in the community, a typical pattern in terms of both tausiyah and fatwas. Every fatwas During the Covid-19 period, which was continued by the Southeast Sulawesi MUI such as Tausiyah or Recommendations, it has accommodated the ijtihad tahqiq al-manat method. Tahqiq al-manat has become mandatory and must be performed by every fiqh expert as well as every individual, in every way, every place, and at every time. Theory ijtihad tahqiq al-manat must be a fundamental reference and one of the factors that scholars consider when determining the law to produce a more comprehensive fatwa in the real world (fiqh al-waqi').